INTRA-ARTICULAR CORTICOSTEROIDS VERSUS PHYSIOTHERAPY IN THE MANAGEMENT OF ADHESIVE CAPSULITIS: Adhesive Capsulitis - Aziz, Tariq; Khan, Atif Ahmed; Akhtar, Noreen; Ayyub, Aisha; Iqbal, Sara; Shafaat, Hina Kanwal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the intra-articular corticosteroid versus physiotherapy in the management of adhesive capsulitis in terms of mean pain score. Study Design: Randomized controlled trial. Place and Duration of Study: Outpatient department, at Armed Forces Institute of Rehabilitation Medicine, from Jul 2013 to Jul 2015. Material and Methods: A total of 90 patients with adhesive capsulitis were enrolled as per inclusion criteria by non probability consecutive sampling. Forty five patients were assigned to group “A” and were given intra-articular injection of triamcinolone 40mg (2ml) and bupivacain 2ml into the shoulder joint. Group “B”, having forty five patients received eight session of physiotherapy on alternate day. Outcome measure included mean pain score using visual analogue scale at six week follow-up. Results: Statistically significant improvement in pain score on visual analogue scale was found in patients with group “A”, with improvement in score from 7.2 ± 0.91 at the start of the study to 5.6 ± 0.18 at six week follow-up (p<0.001). Whereas no statistically significant results were obtained in patients with group “B” having pain score on visual analogue scale of 7.4 ± 0.14 at the start of the study to 7.3 ± 0.14 at six week follow-up (p=0.54). Conclusion: The use of intra-articular corticosteroid injection in shoulder joint potentially offers a significantly greater clinical improvement in pain relief over the use of supervised physiotherapy in the management of patients suffering from adhesive capsulitis.